Evaluation of Alveolo-arterial Oxygen Gradient and Mortality in Different Respiratory Support Methods in Severe COVID-19 Patients Followed in the Intensive Care Unit - Fatih Sargın; Anıl Kuvandık; Simay Karaduman; Hülya Sungurtekin (Galenos Yayinevi, 2023)
Objective:Severe pneumonia is an important cause of mortality in coronavirus disease-2019 (COVID-19) infection. This study evaluated pulmonary gas exchange and mortality according to nasal cannula, high flow nasal cannula, non-invasive positive pressure ventilation and invasive mechanical ventilation used for treating hypoxemic respiratory failure in severe COVID-19 patients.Materials and Methods:Hundred and forty severe COVID-19 patients who were treated in Department of Anesthesiology Intensive Care Unit of Pamukkale University Hospital were reviewed retrospectively. Arterial blood gas results on the 1st, 3rd, 7th, 14th, and 21st days of admission were recorded.Results:The alveolo-arterial oxygen gradient of the patients receiving oxygen via nasal cannula was significantly lower than the patients receiving high-flow nasal cannula, non-invasive and invasive mechanical ventilation. When the other groups were compared, no significant difference was observed between the alveolo-arterial oxygen gradients of the patients who received high-flow nasal cannula, non-invasive and invasive mechanical ventilation support. We observed that the mortality of the patients who were admitted as intubated was significantly higher than the other groups.Conclusion:Invasive and non-invasive oxygen support resulted in similar alveolo-arterial oxygen gradients in severe COVID-19 patients at admission and at 3-week follow-up, but mortality was higher in intubated patients.